(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Coriander (Coriandrum sativum L.) has wide reputation as spice and culinary herb. An experiment was carried out to promote off-season organic coriander leaf cultivation in Bangladesh. The study was conducted at the horticulture farm of Sher-e-Bangla Agricultural University, Dhaka, replicated thrice with two factors; variety (V1Green aroma, V2 Green giant and V3 Indian variety) and organic nutrient source (T0  Control, T1  Cowdung @ 10 t ha-1, T2 Vermicompost @ 3 t ha-1), repeated over five months (March, April, May, June and July) in Randomized Block Design. Data were recorded on several growth and yield parameters. March sown seeds were recorded for highest plant height (19.0 cm), fresh weight of plants per m2 (1359.67 g) and leaf yield (13.6 t ha-1). Results revealed that treatment combination, V2T1 performed better in terms of foliage yield with its best performance (12.17 t ha-1) in March. It was also the best performer for sowing time April (5.14 tha-1), May (3.92 t ha-1) and July (3.16 t ha-1). Asian Australas. J. Biosci. Biotechnol. 2019, 4 (1), 14-23